ANALISIS PARTISIPASI TENAGA KERJA PEREMPUAN DALAM PEMENUHAN KESEJAHTERAAN KELUARGA DI PTKIN SESUMATERA - Yenni Samri Juliati Nasution; Rahmi Syahriza; Marliyah Marliyah (Kafa`ah: Journal of Gender Studies, 2020)
Obligation to fulfill family welfare is the duty of the husband as the head of the family, but women as housewives are allowed to assist the responsibilities of the husband by actively working in the public sector. Women play a dual role not only as a housewife but also as a career woman. This study aims to analyze the participation of women workers in order to fulfilling family welfare in PTKIN in Sumatra. This research is qualitative research with a descriptive approach. Data was collected by interviewing a number of female workers in several PTKIN in Sumatra, namely State Islamic University of Arraniry Banda Aceh, State Islamic University of Sumatera Utara Medan, State Islamic University of Imam Bonjol Padang, and State Islamic University of Raden Fatah Palembang. The results of the research indicate that the participation of women workers in fulfilling family welfare plays an important role. Based on this research, the contribution carried out by women workers can be grouped into three namely: a. Contribute more than 50% in helping fulfill family welfare b. Contribute less than 50% in helping fulfill family welfare c. Contributed to the fulfillment of family welfare by 50%. .